An explanation of one-loop induced h→μτ decay - Seungwon Baek; Takaaki Nomura; Hiroshi Okada (Physics Letters B, 2016)
We discuss a possibility to explain the excess of h→μτ at one-loop level. We introduce three generations of vector-like lepton doublet L′ and two singlet scalars S1,2 which are odd under Z2, while all the standard model fields are even under this discrete symmetry. We show that S1 can be a good dark matter candidate. We show that we can explain the dark matter relic abundance, large part of the discrepancy of muon g−2 between experiments and the standard model predictions, as well as the h→μτ excess of ∼1%, while evading constraints from experiments of dark matter direct detection and charged lepton flavor violating processes. We also consider prospects of production of S2 at LHC with energy s=14 TeV.